Manajemen Masalah Teknologi Informasi Berdasarkan Kerangka Kerja ITIL V3 dan COBIT 5 - Effendy, Faried; Hariyanti, Eva (JSINBIS (Jurnal Sistem Informasi Bisnis), 2018)
In this study, we attempted to develop Information Technology (IT) document of problem management for the export company. This document used as guidance for the companyâ€™s employees to manage IT problem. Not every company's IT division has IT problem management strategy, the priority of problem-solving is usually done by the First In first out (FIFO) method by not considering the impact and the problem urgency. COBIT 5 and ITIL V3 DSS03 related to Problem management were used as standards to review and benchmark on how problem management activities should be done. The output of this research is a Standard Operating Procedure (SOP) document. The Problem management SOP document consists of three stages, the first stage is the preparation of Â SOP with 5 sub-stages, namely: list activity of ITIL V3 and COBIT 5 DSS03, mapping activity of ITIL V3 and COBIT 5 DSS03, verification of company new activities, mapping of activity actor based on RACI DSS02 and mapping of workproduct. The second stage is the adjustment of SOP documents with 2 sub-stages, namely: interviews for identification of needs and mapping of activity actor with the company's organizational structure. The third stage is the verification of SOP documents. The SOP documents contain 11 procedure with five actors. Overall SOP document can eventually become a reference for the company to manage IT problem.Â